Physical Activity and Lifestyle Behaviors in Children and Adolescents - Alexandre Aparecido de Almeida; Matias Noll (MDPI AG, 2024)
A sedentary lifestyle, unfavorable body composition, and low muscle strength are strong predictors of morbidity and mortality and an independent determinant contributing to the development of many chronic diseases [...]